IMPROVING STUDENTSâ PARTICIPATION IN LEARNING READING COMPREHENSION OF NARRATIVE TEXTS THROUGH CONSTRUCTIVE READING MODEL (CRM) - Maenawati, Ida (Language Circle: Journal of Language and Literature, 2013)
This article is a report of an action research project conducted in reading class for Eleventh Year Students of State Senior High School 7 Cirebon in the Academic Year of 2012/2013. The objectives of this study are to describe: (1) the problems faced by the studentsÂ  in learning reading comprehensionÂ  (2)Â  howÂ  Constructive Reading Model is implemented (3) whether Constructive Reading Model improve studentsâ participation in learning readingÂ  comprehension . The result from the questionnaires and observation sheet showed that(1) the studentsÂ  did not actively participate in the process of teaching learning, (2) by using Constructive Reading ModelÂ  studentsâ participation from pre-cycle to cycle 1 increased , from cycle 1 to cycle 2 increased,Â  and (3)Â  studentsâ score ofÂ  reading comprehensionÂ  from pre-cycle to cycle 1 increased 15.65 points, from cycle 1 to cycle 2 increased 11.59 points. SoÂ  the study concluded that the implementation of Constructive Reading ModelÂ  (1) could solve the problems faced by the students in learning reading comprehension (2) could improve studentsâ participation in the process of teaching learningÂ  and(3) could develop studentsâÂ  reading comprehension mastery of the Eleventh Year Students of State Senior High School 7 Cirebon.